2009
DOI: 10.1016/j.biortech.2009.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Removal of hydrogen sulfide using crushed oyster shell from pore water to remediate organically enriched coastal marine sediments

Abstract: Hydrogen sulfide is highly toxic and fatal to benthic organisms as well as causing depletion of dissolved oxygen and generating blue tide in eutrophic coastal seas. The purposes of this study are to reveal adsorption characteristics of hydrogen sulfide onto crushed oyster shell, and to evaluate removal efficiency of hydrogen sulfide from pore water in organically enriched sediments using container experiment in order to develop a coastal sediment amendment. The crushed oyster shell was mainly composed of CaCO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…In this study, the synthetic waste water was prepared according to the procedure reported by Asaoka et al [18]. A portion of Na 2 S.9H 2 O was dissolved in 500 mL solution of 0.01 M KCl purged with N 2 gas.…”
Section: Hydrogen Sulfide Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the synthetic waste water was prepared according to the procedure reported by Asaoka et al [18]. A portion of Na 2 S.9H 2 O was dissolved in 500 mL solution of 0.01 M KCl purged with N 2 gas.…”
Section: Hydrogen Sulfide Solutionmentioning
confidence: 99%
“…A portion of Na 2 S.9H 2 O was dissolved in 500 mL solution of 0.01 M KCl purged with N 2 gas. Thereafter, the pH of the solution was adjusted to 4.5 -5.5 using 0.2 M HCl [18]. The concentration of dissolved H 2 S in water is 4 -6 g/L [11].…”
Section: Hydrogen Sulfide Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, new applications utilizing these wasted oyster shells are expected to contribute towards recycling consciousness within the society [Asaoka et al, 2009]. The application of many kinds of waste shells, which have been dried, crushed and calcined, to sorption of acidic gases and nitrogen oxides is not only economically valuable but also very significant in the aspect of waste recycling.…”
Section: Yearmentioning
confidence: 99%
“…In Japan, 200,000 tons of oysters were produced in 2007 [Asaoka et al, 2009]. And Table 1 shows oyster production of Korea from 1997 to 2006.…”
Section: Introductionmentioning
confidence: 99%